2013
DOI: 10.1371/journal.pone.0057914
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections in HIV Infected and Non-Infected Patients in a Low HIV Prevalence Region, West-Cameroon

Abstract: The magnitude of intestinal parasitic infection in acquired immunodeficiency syndrome patients requires careful consideration in the developing world where poor nutrition is associated with poor hygiene and several tropical diseases. However, there have been very few studies addressing this issue in Cameroon. This study was conducted to determine the prevalence of intestinal parasitosis in HIV/AIDS patients in Dschang -Cameroon. Stool and blood specimens from HIV/AIDS patients and control group were screened r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
45
9
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 10 publications
11
45
9
13
Order By: Relevance
“…Exposure to infection is likely to be higher among adults by reason of greater interaction and adventure with the environment. No helminths were however discovered in the Indonesian study while, Trichuris trichiura, Teania spp and Strongyloides stercoralis were identified in 0.25% cases each of the Cameroonian population studied [11,12]. This paucity of soil transmitted helminths in the latter two studies are consistent with the findings in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Exposure to infection is likely to be higher among adults by reason of greater interaction and adventure with the environment. No helminths were however discovered in the Indonesian study while, Trichuris trichiura, Teania spp and Strongyloides stercoralis were identified in 0.25% cases each of the Cameroonian population studied [11,12]. This paucity of soil transmitted helminths in the latter two studies are consistent with the findings in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Much higher prevalence estimates of 52% and 59.5% were recorded among Indonesian and Cameroonian HIV infected patients respectively [11,12]. The very high prevalence estimates among the Indonesian children can be explained by the fact that they were diarrheal, while the risk factor for higher infection rates in the Cameroon study could have been the age of the participants, who were all adults.…”
Section: Discussionmentioning
confidence: 87%
“…In a study by Nkenfou et al (9) in East Cameroon (2013) on 396 patients (42 HIV-positive patients and 345 HIV-negative patients), the results showed that the overall prevalence of parasitic infections in all patients in this study was equal to 14.64%, while 59.5% of HIV-positive and 9.32% of HIV-negative individuals had gastrointestinal parasitic infections. The most common known parasite in people infected included 19.04% for Cryptosporidium and 22.42% for Entamoeba coli, which may be due to the condition of the disease and quality of drinking water as risk factors for intestinal parasitic infections (9).…”
Section: Discussionsupporting
confidence: 44%
“…The most common known parasite in people infected included 19.04% for Cryptosporidium and 22.42% for Entamoeba coli, which may be due to the condition of the disease and quality of drinking water as risk factors for intestinal parasitic infections (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation